A decomposition of $\boldsymbol{δ}$-open functions - Caldas, Miguel; Jafari, Saeid (Sarajevo Journal of Mathematics, 2024)
In 2008, M. Caldas and G. Navalagi introduced a new class of generalized open functions called weakly $δ$-open functions. By introducing a new type of open functions called relatively weakly $δ$-open together with weakly $δ$-open functions, we establish a new decomposition of $δ$-open functions. 2010 Mathematics Subject Classification. 54A40, 54C10, 54D10; Secondary: 54C08